Analysis of the Implementation of the Inclusive Early Childhood Education Curriculum Model : Case Study at Bright Kiddie Kindergarten Ponorogo, Indonesia - Kusumaningrum, Liana Dyah; Mahardhani, Ardhana Januar; Muttaqin, Muhammad Azam (Jurnal Paedagogy, 2024)
This research aims to analyze the implementation of the inclusive Early Childhood Education curriculum model at Bright Kiddie Kindergarten Ponorogo, Indonesia. This research used a qualitative approach with a case study method. The informants for this research were the school principal, class teacher and teacher accompanying children with special needs. Data collection techniques used were interviews, observation, and documentation. Next, data analysis used interactive model analysis, and for the validity of the research data, the triangulation method was used. The research results showed that Bright Kiddie Kindergarten had children with special needs with different characteristics, needs and abilities. In implementing inclusive learning, the school used regular and pull-out class models with duplication, simplification, substitution and omission curriculum models according to the needs of each student with special needs. Children with special needs study with other children in regular classes. However, at certain times, they will be moved to another room to receive additional learning from special accompanying teachers. The curriculum model was also adjusted based on the identification and assessment results of each child with special needs as a basis for appropriate learning planning. Some duplicate the same curriculum as normal children (duplication), some simplify it without eliminating the substance (simplification), some replace it with equivalent material (substitution), and there are those who change it completely to suit the needs of each child.